The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcell.2021.633819
|View full text |Cite
|
Sign up to set email alerts
|

Novel Truncating and Missense Variants in SEMA6B in Patients With Early-Onset Epilepsy

Abstract: Progressive myoclonic epilepsy (PME) is a rare neurodegenerative disease, characterized by myoclonic seizures and tonic clonic seizures, with genetical and phenotypical heterogeneity. The semaphorin 6B (SEMA6B) gene has been recently reported a causal gene of PME. Independent studies are warranted to further support these findings. Here we report that one nonsense variant in NM_032108.3 exon17 c.2056C > T (p.Gln686∗) and one missense variant in exon14 c.1483G > T (p.Gly495Trp) of SEMA6B, both occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…All variants reported to date are truncation variants in the last exon of the gene, except for the c.1483G>T variant ( 16 ). The only missense mutation c.1483G>T, which was reported by Xiaozhen et al ( 16 ), was identified de novo in a 3-year-old boy who had apparently normal developmental milestones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All variants reported to date are truncation variants in the last exon of the gene, except for the c.1483G>T variant ( 16 ). The only missense mutation c.1483G>T, which was reported by Xiaozhen et al ( 16 ), was identified de novo in a 3-year-old boy who had apparently normal developmental milestones.…”
Section: Discussionmentioning
confidence: 99%
“…All variants reported to date are truncation variants in the last exon of the gene, except for the c.1483G>T variant ( 16 ). The only missense mutation c.1483G>T, which was reported by Xiaozhen et al ( 16 ), was identified de novo in a 3-year-old boy who had apparently normal developmental milestones. This child was referred to the hospital at the age of 2 years because of the onset of seizures with eye-rolling, cyanotic lips, consciousness lapses, and right upper limb jitter as well as a gelastic seizure lasting > 15 s. Furthermore, he had good response to combination treatment of levetiracetam and sodium valproate with no recurrence noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An IDTxGen ® Exome Research Panel (IDT, United States) was used to capture the exons, and HiseqX10 (Illumina, United States) was used to sequence the DNA fragments. FASTQ data analysis was conducted as described in previous studies ( Xiaozhen et al, 2021 ). The candidate pathogenic genes were confirmed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…2019R071-F03). Variants calling and interpretation have been described elsewhere ( Xiaozhen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%